An exploration of young people's narratives of hope following experience of psychosis. Issue 2 (3rd April 2018) - Bonnett, Victoria; Berry, Clio; Meddings, Sara; Holttum, Sue
ABSTRACT: Aims: To expand understandings of how young people with psychosis experience hope. This included to which factors young people attributed changes in their hopefulness and the role played by professionals and others with lived experience. Method: Ten young people recovering from an experience of psychosis were interviewed using narrative methodology. Results: The experience of hope as an overarching strand throughout the narratives had three common elements: sense of belonging, which included social inclusion, the importance of information and the significance of planning and occupation. Professionals played an important role in facilitating small steps forwards. Conclusions: The findings suggest the importance to young people of a sense of belonging and achieving small goals to facilitate hopeful thinking and, for clinicians, the value of supporting new peer relationships and meaningful occupation.